USE OF EDUCATIONAL TECHNOLOGIES IN PREPARING FUTURE TEACHERS FOR INNOVATIVE ACTIVITY - Amirkhanova Diana Nurmakhanovna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The modern education system requires the formation of a creative person who can independently receive new information, evaluate it and draw appropriate conclusions